NEW
New Website Launch
Experience the best way to solve previous year questions with mock tests (very detailed analysis), bookmark your favourite questions, practice etc...
1

WB JEE 2010

MCQ (Single Correct Answer)

G.M. and H.M. of two numbers are 10 and 8 respectively. The numbers are

A
5, 20
B
4, 25
C
2, 50
D
1, 100

Explanation

Let nos. be a and b

(A = A.M., G = G.M., H = H.M.)

Here, G = 10, H = 8

$$\because$$ G2 = AH $$\Rightarrow$$ 100 = 8A

$$\therefore$$ $$A = {{25} \over 2}$$

$$\therefore$$ ab = 100 & a + b = 25, which are satisfied by option (a) only.

2

WB JEE 2010

MCQ (Single Correct Answer)

Sum of n terms of the following series 13 + 33 + 53 + 73 ......... is

A
n2(2n2 $$-$$ 1)
B
n3(n $$-$$ 1)
C
n3 + 8n + 4
D
2n4 + 3n2

Explanation

$${1^3} + {3^3} + {5^3} + ....$$ to n terms

$$ = {1^3} + {3^3} + {5^3} + .... + {(2n - 1)^3}$$

$$ = \{ {1^3} + {2^3} + {3^3} + .... + {(2n)^3}\} - \{ {2^3} + {4^3} + {6^3} + .... + {(2n)^3}\} $$

$$ = {\left\{ {{{2n(2n + 1)} \over 2}} \right\}^2} - {2^3}\{ {1^3} + {2^3} + {3^3} + ... + {n^3}\} $$

$$ = {n^2}{(2n + 1)^2} - 8{\left\{ {{{n(n + 1)} \over 2}} \right\}^2}$$

$$ = {n^2}\{ (4{n^2} + 4n + 1) - 2{(n + 1)^2}\} = {n^2}(2{n^2} - 1)$$

3

WB JEE 2010

MCQ (Single Correct Answer)

If sum of an infinite geometric series is $${4 \over {3}}$$ and its 1st term is $${3 \over {4}}$$, then its common ratio is

A
$${7 \over {16}}$$
B
$${9 \over {16}}$$
C
$${1 \over 9}$$
D
$${7 \over 9}$$

Explanation

Here, $$a = {3 \over 4}$$, $${S_\infty } = {4 \over 3}$$

$$\therefore$$ $${a \over {1 - r}} = {4 \over 2} \Rightarrow 3a = 4 - 4r$$

$$ \Rightarrow {9 \over 4} = 4 - 4r$$

$$\therefore$$ $$r = {7 \over {16}}$$

4

WB JEE 2009

MCQ (Single Correct Answer)

The sum of the infinite series $$1 + {1 \over {2!}} + {{1\,.\,3} \over {4!}} + {{1\,.\,3\,.\,5} \over {6!}} + \,....$$ is

A
e
B
e2
C
$$\sqrt e$$
D
1/e

Explanation

$$1 + {1 \over {2!}} + {{1\,.\,3} \over {4!}} + {{1\,.\,3\,.\,5} \over {6!}} + \,....$$

tn of $${1 \over {2!}} + {{1\,.\,3} \over {4!}} + {{1\,.\,3\,.\,5} \over {6!}} + \,......$$ is

$${t_n} = {{1\,.\,3\,.\,5\,.\,......\,.\,(2n - 1)} \over {(2n)!}}$$

$$ = {{1\,.\,2\,.\,3\,.\,4\,.\,5\,.\,6\,.\,......\,(2n - 1)\,.\,(2n)} \over {2\,.\,4\,.\,6\,.\,.....\,(2n)\,(2n)!}}$$

$$ = {{(2n)!} \over {(1\,.\,2\,.\,3\,.\,.....\,.\,n)(2n)!}} = {1 \over {{2^n}(n!)}}$$

$$\therefore$$ Sum $$ = 1 + \sum\limits_{n = 1}^\infty {{t_n} = 1 + {1 \over {2(1!)}} + {1 \over {{2^2}(2!)}} + {1 \over {{2^3}(3!)}} + .....} $$

$$({e^x} = 1 + {x \over {1!}} + {{{x^2}} \over {2!}} + {{{x^3}} \over {3!}} + .....)$$

$$ = {e^{1/2}}$$

Joint Entrance Examination

JEE Main JEE Advanced WB JEE

Graduate Aptitude Test in Engineering

GATE CSE GATE ECE GATE EE GATE ME GATE CE GATE PI GATE IN

Medical

NEET

CBSE

Class 12